Synthesis of (+) and (‐)‐Streptomyces coelicolor Butanolide 5 (SCB‐5). Issue 22 (15th June 2021) - Donges, Jonas; Hofmann, Sandra; Brüggemann, Moritz; Frank, Andrea; Schollmeyer, Dieter; Nubbemeyer, Udo
Abstract: Various 1‐(1‐hydroxyalkyl) paraconyl alcohols are important signaling molecules within antibiotics production in Streptomyces sp. Intending developing a flexible convergent chemical synthesis of such butanolides, a zwitterionic aza‐Claisen rearrangement was chosen as reliable strategy generating the central stereotriad. Reaction of enantiopure N ‐allyl pyrrolidines and 4‐phenylbutenoic acid fluoride delivered defined configured amides displaying the 2, 3, 1' stereotriads. The configuration was determined by the allyl alcohol moiety indicating a complete remote stereo control. Amide removal by iodolactonization and proceeding reductions, halocyclization and elimination gave key alkylidene tetrahydrofuran derivatives. Stepwise degradation of the olefins through ozonolysis, reductive work‐up and protecting group removal delivered both enantiomers of the target Streptomyces coelicolor butanolide 5. Abstract : A diastereoselective total synthesis of (+) and (−) Streptomyces coelicolor butanolides SCB‐5 has been developed. Starting from suitable allylamines and acyl fluorides, a zwitterionic aza‐Claisen rearrangement delivered amides displaying the key stereotriades with defined configurations. Stepwise oxidative degradation of the double bonds and subsequent regioselective cyclization afforded the enantiopure target butanolides.